Mapeamento funcional dos efeitos da estimulação cerebral profunda no núcleo anterior da tálamo - Gimenes, Christiane [UNIFESP] (2018)
Deep brain stimulation (DBS) refers to the delivery of electric current to specific deep brain structures through implanted electrodes. DBS to the anterior nucleus of thalamus (ANT) is a safe and effective alternative treatment for medically refractory seizures that was recently approved for use in United States. Despite the antiseizure effects of ANT DBS, preclinical and clinical studies have failed to demonstrate it actions at a whole brain level. Here, we used a magnetic resonance imaging (MRI)based approach in healthy adult rats to investigate the effects of ANT DBS through the circuit of Papez, which is a circuit that is wellstudied in temporal lobe epilepsy (TLE). After ANT electrode implantation and recovery, ANT DBS and SHAM (sham animals had electrodes implanted but were not stimulated) rats received one single injection of the contrast enhancer, manganese chloride (60 mg/kg, ip). Twelve hours after, rats underwent the baseline scan using the MEMRI (Manganeseenhanced magnetic resonance imaging) technique. DBS was immediately delivered during 1h (130 Hz and 200 μA) and followed by the same MEMRI sequence. Perfusion was followed by subsequent cFos immunostaining of brain sections. Acute unilateral ANT DBS significantly reduced the overall manganese uptake and consequently, the MEMRI contrast in the circuit of Papez. Additionally, cFos expression was bilaterally increased in the cingulate cortex and posterior hypothalamus, areas directly connected to ANT, as well as in amygdala and subiculum, within the limbic circuitry. Our data indicate that MEMRI can be used to detect wholebrain responses to DBS, as the high frequency stimulation parameters used here caused a significant reduction of cell activity in the circuit of Papez that might help to explain the antiepileptic effects of ANT DBS.